Identification of a Novel Inhibition Site in Translocase MraY Based upon the Site of Interaction with Lysis Protein E from Bacteriophage ϕX174. Issue 9 (4th June 2014) - Rodolis, Maria T.; Mihalyi, Agnes; O'Reilly, Amy; Slikas, Justinas; Roper, David I.; Hancock, Robert E. W.; Bugg, Timothy D. H.
Abstract Translocase MraY is the site of action of lysis protein E from bacteriophage ϕX174. Previous genetic studies have shown that mutation F288L in transmembrane helix 9 of E. coli MraY confers resistance to protein E. Construction of a helical wheel model for transmembrane helix 9 of MraY and the transmembrane domain of protein E enabled the identification of an Arg‐Trp‐x‐x‐Trp (RWxxW) motif in protein E that might interact with Phe288 of MraY and the neighbouring Glu287. This motif is also found in a number of cationic antimicrobial peptide sequences. Synthetic dipeptides and pentapeptides based on the RWxxW consensus sequence showed inhibition of particulate E. coli MraY activity (IC50 200–600 μM), and demonstrated antimicrobial activity against E. coli (MIC 31–125 μg mL−1). Cationic antimicrobial peptides at a concentration of 100 μg mL−1 containing Arg‐Trp sequences also showed 30–60 % inhibition of E. coli MraY activity. Assay of the synthetic peptide inhibitors against recombinant MraY enzymes from Bacillus subtilis, Pseudomonas aeruginosa, and Micrococcus flavus (all of which lack Phe288) showed reduced levels of enzyme inhibition, and assay against recombinant E. coli MraY F288L and an E287A mutant demonstrated either reduced or no detectable enzyme inhibition, thus indicating that these peptides interact at this site. The MIC of Arg‐Trp‐octyl ester against E. coli was increased eightfold by overexpression of mraY, and was further increased by overexpression of the mraY mutant F288L, also consistent with inhibition at the RWxxW site. As this site is on the exterior face of the cytoplasmic membrane, it constitutes a potential new site for antimicrobial action, and provides a new cellular target for cationic antimicrobial peptides.